2005
DOI: 10.1073/pnas.0405775102
|View full text |Cite
|
Sign up to set email alerts
|

Longer lifespan, altered metabolism, and stress resistance in Drosophila from ablation of cells making insulin-like ligands

Abstract: The insulin͞insulin-like growth factor-like signaling pathway, present in all multicellular organisms, regulates diverse functions including growth, development, fecundity, metabolic homeostasis, and lifespan. In flies, ligands of the insulin͞insulin-like growth factor-like signaling pathway, the Drosophila insulin-like peptides, regulate growth and hemolymph carbohydrate homeostasis during development and are expressed in a stage-and tissue-specific manner. Here, we show that ablation of Drosophila insulin-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
856
10
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 738 publications
(917 citation statements)
references
References 63 publications
(105 reference statements)
50
856
10
1
Order By: Relevance
“…This finding is consistent with results from mammalian studies, which have shown reduction of insulin-like grow factor-1 (IGF-1) by supplementation of resveratrol in diets Baur 2010). In Drosophila, reducing the levels of dIlp2, dIlp3, and dIlp5 by partial ablation of insulinlike peptide-producing median neurosecretory cells in the brain resulted in longer lifespan and increased resistance to oxidative stress (Broughton et al 2005). In the present study, we have also shown that under the low sugar-high protein and high-fat diet conditions, supplementation of resveratrol leads to lower transcript levels of several oxidative stress response Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with results from mammalian studies, which have shown reduction of insulin-like grow factor-1 (IGF-1) by supplementation of resveratrol in diets Baur 2010). In Drosophila, reducing the levels of dIlp2, dIlp3, and dIlp5 by partial ablation of insulinlike peptide-producing median neurosecretory cells in the brain resulted in longer lifespan and increased resistance to oxidative stress (Broughton et al 2005). In the present study, we have also shown that under the low sugar-high protein and high-fat diet conditions, supplementation of resveratrol leads to lower transcript levels of several oxidative stress response Fig.…”
Section: Discussionsupporting
confidence: 89%
“…However, six genes were found down-regulated by resveratrol. Among them are Drosophila insulin-like peptide 3 and 5 (dIlp3 and dIlp5) involved in insulin-like signaling, which is a major pathway known to modulate lifespan in worms, flies, and rodents (Broughton et al 2005;Fontana et al 2010). Supplementation of resveratrol also downregulated glutathione S transferase D1 (GstD1) and heat shock protein 68, two downstream targets of Jun kinase (JNK) signaling pathway, which is a major oxidative stress response pathway and is known to modulate lifespan in several model organisms (Wang et al 2005;Karpac and Jasper 2009).…”
Section: Influence Of Dietary Composition On the Effect Of Resveratromentioning
confidence: 99%
“…Studies in yeast and higher eukaryotes have shown that lowered TOR (and/or decreased IIS in higher eukaryotes) signaling pathway activity increases lifespan (Kenyon et al, 1993;Guarente and Kenyon, 2000;Vellai et al, 2003;Hwangbo et al, 2004;Kapahi et al, 2004;Kaeberlein et al, 2005;Powers et al, 2006). In addition, decreased IIS/TOR signaling activity is associated with increased resistance to some types of stress, suggesting that this pathway plays also an important role in the adaption to different stress conditions (Scott et al, 2002;Holzenberger et al, 2003;Broughton et al, 2005;Teleman et al, 2005;Tettweiler et al, 2005;Powers et al, 2006). In the following section, we will review extra-and intracellular cues that modulate TOR signaling.…”
Section: Stress and Mtormentioning
confidence: 99%
“…For example, ablation of insulin-producing cells leads to diabetic flies and, conversely, flies in which AKH-producing cells have been ablated have low levels of circulating sugars 3,12 . Further, proper mobilization of fat from the fat body is perturbed in the absence of oenocytes-an interaction reminiscent of the crosstalk between hepatocytes and adipocytes in humans 9,13 .…”
Section: Metabolic Homeostasismentioning
confidence: 99%